EOC women and shiftwork : protective legislation survey, 1977 (UK Data Service, 1982)
The (first) survey to explore women's attitudes and intentions concerning hours of work and the legislation affecting them, carried out by the Equal Opportunities Commission as part of its statutory duty to review the legislation which affects the hours women may work in industry.